PENGARUH CURRENT RATIO, EARNING PER SHARE (EPS), RETURN ON EQUITY (ROE), DAN RETURN ON TOTAL ASSETS (ROA) TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR PERKEBUNAN YANG MASUK PERHITUNGAN INDEKS SAHAM SYARIAH INDONESIA (ISSI) DI BURSA EFEK INDONESIA (BEI) PERIODE 2014 – 2017 - Lisnawati Lisnawati; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2019)
The development of capital market in a country has a major role in the economy including Indonesia such as the Islamic capital market. Some of the companies are count in the Indonesian Sharia Stock Index (ISSI) and one of them in the agricultural sector. Among the agricultural sector, the most sharia stock is owned by the plantation sub sector. The study aims to test with partial and simultaneous the influence of Current Ratio, Earning Per Share (EPS), Return On Equity (ROE), and Return On Total Assets (ROA) against stock prices. This research use secondary data from annual report who has publies in the Indonesia Stock Exchange (IDX). The population of this research has eight companies. Analytical techniques use simple and multiple linear regressions. The research indicates that partial variable Earning Per Share (EPS) and Return On Total Assets (ROA) had a significant effect against stock prices, while Current Ratio and Return On Equity (ROE) had no significant against stock prices. Simultaneously variable Current Ratio, Earning Per Share (EPS), Return On Equity (ROE), and Return On Total Assets (ROA) had a significant effect against stock price.